Classification of soil sites and response spectra for Chennai city - Kamatchi, P.; Rao, K. Balaji; Anoop, M. B.; Iyer, Nagesh R. (Journal of Structural Engineering, 2025)
Response spectra of a soil site is different from that of rock site, same is being accounted by three different shapes of spectra in Indian seismic code. In International Building Code (IBC) effect of soil type is accounted by response spectra generated using amplification factors based on top 30 m shear wave velocity. These amplification factors are arrived from recorded ground motions for lower peak ground accelerations and by using analytical procedures for higher peak ground accelerations. Analytical/numerical procedures require strong ground motions at rock level and complete bore log details of soil site. In the absence of complete information, based on the collected data classification is done for typical sites of Chennai city. Surface response spectra for Chennai city are obtained using amplification functions for a scenario earthquake. Surface response spectra for Chennai city are also obtained using amplification functions for a risk consistent earthquake of 2% probability of exceedance in 50 years. Present study, has brought out the importance of inclusion of classification of soil sites and amplification factors in the seismic code.